The Effect of Skimming Reading Technique on Students’ Reading Comprehension in Analytical Exposition Text - Reza Aliza Sonia; Roswati (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
Reading is one of the most important language skills to be learned and mastered by learners of English as a second language. Skimming reading technique is the technique used by the researcher to improve students' reading comprehension in analytical exposition text. This study aims to examine the significant effect of skimming reading technique on students' reading comprehension in analytical exposition text. This research was conducted using the pre-experimental one group pre-test post-test method, with a sample size of 30 students, the sample selection used purposive sampling technique. In collecting data, researchers used multiple choice questions as instruments. In analyzing the data, the researcher used the Paired Sample T Test using the SPSS version 23 program. The results showed that there was a significant influence between students' reading comprehension on analytical exposition text before and after using skimming reading techniques, where the sig (2-tailed) value of 0.000 was smaller than 0.05, then Ha was accepted and Ho was rejected.